The Development of a Local Wisdom-Based RADEC Model to Enhance Elementary School Students’ Cultural Literacy and Collaboration Skills - Emi Sulistri; Evinna Cinda Hendriana; Dina Anika Marhayani; Mertika Mertika; Rien Anitra; Wasis Suprapto; Charito Agravante Quiñones (FKIP Universitas Lampung, 2026)
The low levels of cultural literacy and collaboration skills among elementary school students in a multicultural city like Singkawang pose a 21st-century challenge. This challenge can be overcome through innovative learning models, including the TiDayu local-wisdom-based RADEC. The objectives of this study are to determine the validity, practicality, and effectiveness of the local wisdom–based RADEC model in enhancing the cultural literacy and collaboration skills of elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model approach. The subjects of the study were fifth-grade students of SDN 89 Singkawang. Data were collected through questionnaires, tests, and observations, analyzed descriptively, and using N-Gain. The results of this study indicate that the average validation scores from learning model experts, science content experts, cultural experts, and practitioner experts (elementary school teachers) place the local wisdom–based RADEC model in the valid category (84.6%). Based on implementation data and teacher and student responses, the RADEC model was considered practical, with an average score of 83.2%. Furthermore, the implementation of the local wisdom-based RADEC model indicates its potential effectiveness in learning, as evidenced by an increase in student literacy with an N-Gain score of 0.75 (high category). The average students’ collaborative skills increased from 56.25% (categorized as moderate collaboration) to 95.99% (categorized as very high collaboration). Therefore, the TiDayu local wisdom-based RADEC model is easy to implement and shows initial potential to enhance students’ cultural literacy and collaboration skills, as local wisdom provides a meaningful learning context, enables the interpretation of cultural values (cultural meaning-making), and encourages social interaction among elementary school students. Keywords: RADEC model, local wisdom, cultural literacy, collaboration skills.